Cultivating religious moderation through a Kurikulum Berbasis Cinta: A teacher’s strategy in a Bali Muslim-minority madrasah - Haris Nursyah Arifin; Rusmayani Rusmayani; Arjiman Arjiman; Moh Hafid (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
The persistence of intolerance in Indonesia makes cultivating religious moderation through madrasah education urgent, particularly in Muslim minority regions where Islamic education must preserve faith identity while sustaining interfaith harmony. This study seeks to explore teachers’ perceptions and conceptual understandings of the Kurikulum Berbasis Cinta (Love-Based Curriculum) and religious moderation, investigate the pedagogical strategies employed to embed moderation values within learning processes, and interpret how these values are contextualized through Balinese local wisdom in a Muslim minority madrasah setting. Employing a qualitative case study at MA Al-Amin Tabanan, Bali, data were collected through in-depth interviews with teachers, the principal, students, religious leaders, and parents, complemented by participant observation and document analysis. The findings show, first, that teachers understand the Love-Based Curriculum and religious moderation as one integrated framework in which the graduate profile dimensions and the Panca Cinta (five loves) are mapped onto the four moderation indicators. Second, teachers integrate moderation values through Panca Cinta-based habituation, lesson planning that embeds the moderation indicators, experiential and problem-based learning, and the management of sensitive discussions supported by contextual media. Third, learning is contextualized with Balinese local wisdom, particularly Menyama Braya and Tri Hita Karana, and through arts programs such as Hadrah-Gamelan. The originality of this study lies in revealing that a minority context sharpens, rather than weakens, the operationalization of moderation values through teachers’ deliberate mapping of curriculum dimensions onto moderation indicators. The research contributes to multicultural Islamic education models in minority contexts and to madrasah curriculum development in diverse societies.